Producing liquid organic fertilizer (LOF) by combining rice straw waste with local microorganisms (MOL) to enhance the growth of rice plants - Adityas Agung Ramandani; Shintawati Shintawati; Salomo P Aji (Jurnal Teknik Kimia, 2024)
Rice straw is a byproduct of rice harvesting that is often underutilized or discarded, contributing to agricultural waste. Finding effective ways to utilize rice straw could reduce waste and potentially enhance agricultural productivity. This study investigates the impact of rice straw and Local Microorganisms (MOL) on rice plant growth through liquid organic fertilizer (LOF). Employing a 2 x 2 factorial randomized regular two-level factorial design with three replications and blocks, the study assessed the impact of varying levels of rice straw (50 grams and 100 grams) and MOL application (200 mL and 400 mL) on rice plant height over a 7-day period. Results indicate that the combination of 50 grams of rice straw and 200 mL of MOL yielded the highest average plant height of 4.91 cm. Notably, MOL (B) exerted the most substantial influence on plant height, with the interaction between rice straw (A) and MOL also contributing, albeit to a lesser degree. Optimization analysis identified the optimal combination of 50 grams of rice straw and 266 mL of MOL for maximizing rice plant growth, underscoring the potential of integrating these elements into agricultural practices. This approach not only mitigates agricultural waste but also reduces dependence on chemical fertilizers, aligning with principles of sustainable agriculture. Moreover, the study robust experimental design and statistical analysis using Design Expert Version 13 validate the reliability and applicability of these findings in agricultural settings.